Philosophy of Communication in Reading Contemporary Digital Media:: Power, Post-Truth, and Ethical Challenges - Abdi Susanto (Gerakan Indonesia Kita, 2026)
The rapid expansion of digital media has profoundly transformed the ways human beings communicate, construct social relations, and understand reality. Media can no longer be understood merely as technical instruments for transmitting information; rather, they function as symbolic and political spaces in which meaning, power, and ideology are continuously produced and contested. This article examines contemporary digital media from the perspective of the philosophy of communication, focusing on the interrelation between media, power, and the phenomenon of post-truth in the modern public sphere. Employing a conceptual research method grounded in philosophical and critical analysis, this study engages key thinkers in communication philosophy and critical theory, including Marshall McLuhan, Jürgen Habermas, Jean Baudrillard, Michel Foucault, and Antonio Gramsci. The analysis demonstrates that digital media are fundamentally ambivalent: while they expand participation and democratize communicative practices, they simultaneously intensify algorithmic control, information fragmentation, and social polarization. The article argues that the philosophy of communication provides an indispensable normative and critical framework for developing media ethics and reimagining a more humanistic, dialogical, and just digital public sphere in the age of artificial intelligence and big data.